2021
DOI: 10.1016/j.micpath.2021.105086
|View full text |Cite
|
Sign up to set email alerts
|

Partial protection of Sinopharm vaccine against SARS COV2 during recent outbreak in Bahrain

Abstract: Background In order to impart immunity against SARS COV 2 in the community, the oil rich countries of the Gulf Cooperation Council (GCC) provided citizens and expatriates with free vaccination. Different types of vaccination brands were utilized for this purpose. The purpose of this study is to determine the efficacy of the different types of vaccinations used. Methods This is an observational analytical case study of one Bahraini family who were vaccinated with 1st, 2n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…An even weaker performance was observed for the Sinopharm vaccine. In line with our data, a recent study in Bahrain showed that in a group of 22 persons vaccinated with a double dose of the Sinopharm vaccine, 20 were infected with SARS-CoV-2 31 . Saeed et al, after analyzing the expression of spike-speci c antibody levels in 2868 COVID-19 vaccinated individuals with the Sinopharm vaccine in Iran, came to the conclusion that two doses of Sinopharm may not be adequate to provide long-lasting immunity against SARS-CoV-2 32 .…”
Section: Discussionsupporting
confidence: 92%
“…An even weaker performance was observed for the Sinopharm vaccine. In line with our data, a recent study in Bahrain showed that in a group of 22 persons vaccinated with a double dose of the Sinopharm vaccine, 20 were infected with SARS-CoV-2 31 . Saeed et al, after analyzing the expression of spike-speci c antibody levels in 2868 COVID-19 vaccinated individuals with the Sinopharm vaccine in Iran, came to the conclusion that two doses of Sinopharm may not be adequate to provide long-lasting immunity against SARS-CoV-2 32 .…”
Section: Discussionsupporting
confidence: 92%
“…As a response to the study, the country started giving boosters of the Pfizer vaccine to Sinopharm vaccine recipients. It concluded that the Sinopharm vaccine does not prevent people from getting infected [217]. Another study of the Sinopharm/BBIBP-CorV vaccine showed that the vaccine could induce an antibody response in 95% of participants, although the seroconversion rate was lower in older individuals (>60 years).…”
Section: Efficiency Of Vaccines Observed After Phase 3 Trialmentioning
confidence: 99%
“…Partial protection against SARS COV 2 infection is provided by Sinopharm. This might be related to the absence of its ability to identify recent changes in the protein structure of spike(S) viral protein [15]. Our study showed that out of total 40 people enrolled in the study, 19 (47.5%) showed seroconversion after 2 weeks of first dose; 8 (36%) were vaccinated with sinopharm and 11 (61.1%) were vaccinated with sinoVac.…”
Section: Discussionmentioning
confidence: 80%